The Arts and Public Health: Changing the Conversation on Health - Galea, Sandro (Health promotion practice, 2021)
This argument rests on how we define public health. Fundamentally public health is a collective act, aimed at assuring that populations are as healthy as possible (Institute of Medicine, 1998). This then requires a reckoning with what it is that makes populations healthy to begin with. The health of populations is a product of multiple levels of influence. Political decisions begat policies that ultimately affect health. Our health is influenced by the conditions of the cities in which we live and by the state of our neighborhoods and the places where we live, work, and play. While our behaviors, whether we exercise, eat healthy foods, or refrain from risky behaviors, clearly have a role in shaping our health, many of these behaviors are constrained and are shaped by these same environments. We are more likely to exercise if we are living in a safe neighborhood where we can walk without fear of personal harm. Therefore, the health of populations is a product as much of the world around us, the conditions that characterize where we live and how we live, than it is about personal characteristics or, certainly, genetic predispositions.